1996
DOI: 10.1080/01635589609514491
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultraviolet light‐induced skin carcinogenesis and ornithine decarboxylase activity in Sencar and Hairless SKH‐1 mice fed a constant level of dietary lipid varying in corn and coconut oil

Abstract: To investigate the effect of various levels of corn oil and coconut oil on ultraviolet (UV) light-induced skin tumorigenesis and ornithine decarboxylase (ODC) activity, Sencar and SKH-1 mice were fed one of three 15% (weight) fat semipurified diets containing three ratios of corn oil to coconut oil: 1.0%:14.0%, 7.9%:7.1%, and 15.0%:0.0% in Diets A, B, and C, respectively. Groups of 30 Sencar and SKH-1 mice were fed one of the diets for three weeks before UV irradiation; then both strains were UV irradiated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…After one month on the diets (i.e., the mice were then 8 wk of age) the average body weights of mice fed Diets L, M, and H were 38.0 ± 1.4,40.8 + 3.9, and 39.5 ± 0.7 (SD) g, respectively. There were thus no significant differences in body weight between the diet groups in the study, and this is corroborated by the results of an earlier study using the same diets fed to Sencar mice (24).…”
Section: Diet Studysupporting
confidence: 89%
See 1 more Smart Citation
“…After one month on the diets (i.e., the mice were then 8 wk of age) the average body weights of mice fed Diets L, M, and H were 38.0 ± 1.4,40.8 + 3.9, and 39.5 ± 0.7 (SD) g, respectively. There were thus no significant differences in body weight between the diet groups in the study, and this is corroborated by the results of an earlier study using the same diets fed to Sencar mice (24).…”
Section: Diet Studysupporting
confidence: 89%
“…The role of linoleate in phorbol ester-induced skin tumor promotion has been of interest, because it is the substrate for the synthesis of arachidonate and also because it can compete with arachidonate for incorporation into the ín-2-position of phospholipids and for lipoxygenase metabolism, which gives rise to hydroxy derivatives, which have been shown to modulate proliferation and differentiation (23). Phosphatidylcholine linoleate was increased in mice fed the 7.9% and 15.0% corn oil diets compared with animals fed the 1.0% corn oil diet; phosphatidylcholine arachidonate remained the same or decreased slightly as dietary corn oil increased (24).…”
Section: Introductionmentioning
confidence: 88%
“…SKH1 mice are highly susceptible to UVR induced skin cancer [77]; this susceptibility may be a function of the hairless gene itself, as C3H hairless mice are more susceptible to UVR carcinogenesis than haired mice of the same strain [78]. The SKH1 hairless mouse develops lesions resembling UVR-induced tumors in man and can be employed in studies that yield quantitative data suitable for both mechanistic studies and risk assessment purposes.…”
Section: Skin Carcinogenesis In Hairless Micementioning
confidence: 99%
“…It has also been shown that UVB irradiation leads to cell proliferation in vivo (12). The consequent effect of UVBinduced cell proliferation might lead to tumorigenesis (13). Huang et al (14) reported that UVB irradiation induced AP-1 transactivation in a mouse epithelial cell line.…”
mentioning
confidence: 99%